What do we know about globalization? issues of poverty and income distribution - Dehesa, Guillermo de la (Blackwell Pub, 2007)
This book examines the two fundamental arguments that are often raised against globalization: that it produces inequality and that it increases poverty. Here Guillermo De la Hesa, Chairman of the Centre for Economic Policy Research (CEPR) and a member of the Group of Thirty, and a leading figure in economics explains the ways in which wealthy nations and developing countries alike have failed to implement changes that would result in a reversal of these social ills, and also dispels the notion of the so-called "victim of globalization", demonstrating how, despite popular belief, acceleration of globalization actually stands to reduce the levels of poverty and inequality worldwide. He poses the question as to whether increased technological, economic, and cultural change can save the world from international income inequality, and by extension, further violence, terrorism and war